Analisis Tradisi Melemang dalam Kajian Etnomatematika Dan Penerapannya dalam Pembelajaran Matematika - Wahyu Fitroh (Universitas Batanghari Jambi, 2020)
The understanding of values in mathematics learning delivered by the teachers has not touched all possible aspects. Mathematics is seen as a tool to solve practical problems in the world of science alone, thus ignoring the view of mathematics as a human activity (Soedjadi, 2007). That view is not wrong at all, both are correct and in accordance with the growth of mathematics itself. However, due to or the impact of routine mathematics teaching so far, the view that states mathematics solely as a tool becomes inappropriate in the process of education of the nation's children. It often happens that the teacher places more emphasis on teaching the tool, the teacher tells or shows the tool, how the tool is used, how the child learns to use it, without knowing how the tool was made or without criticizing why the tool is used. In fact, not a few teachers are hooked to meet the target of high test scores so that many other values that are far more important for students are forgotten. The process of mathematics education as it is very possible for children to only memorize without understanding, even though they should be able to memorize only after understanding. Based on the description above in this study, the author explains the process of how to make lemang and how to lemang in learning mathematics, so the purpose of this study is to describe and identify mathematics learning in the tradition of melemang kerinci community, namely the community of Three villages (Koto Lolo, Koto Bento, Koto Tengah) Pesisir Bukit Kota Sungai Penuh District. This type of research is a qualitative research with a phenomenological approach that aims to get as complete information as possible about the implementation of ethno-mathematics in mathematics learning. Data collection methods using observation, interviews, and documentation techniques, then analyzed. The results show that in the tradition of melemang there is mathematics learning in the form of: 1. Tube Elements, 2. Tube Nets, 3. Tube Area, 4. Tube Volume which is part of the material from the Education Unit Level Curriculum (KTSP), School Level First Intermediate (SMP) in class IX Semester I and 5. Social Arithmetic in class VIII Semester I so that it can be concluded that the results of the study show that there is a community tradition of conducting mathematical activities and the application of ethnomatatics as a means to motivate, stimulate students, can overcome boredom and provide new nuances in mathematics learning. This research focuses on only one object sub-study. it is expected that further research will be further developed on other types and cultural traditions of the community and be assessed in order to be more efficient and effective in their discussions (in-depth and directed).